2008
DOI: 10.1002/ptr.2451
|View full text |Cite
|
Sign up to set email alerts
|

Herba Epimedii water extract elevates estrogen level and improves lipid metabolism in postmenopausal women

Abstract: Hormone replacement therapy (HRT) can ameliorate lipid metabolism after menopause, but it is not suitable for long-term use because of serious side effects. Herba Epimedii is a widely used herbal medicine in many Asian countries, it potentially treats menopausal syndrome and its complications with few side effects and good curative effects. The study aimed to evaluate the effects of Herba Epimedii water extract on blood lipid and sex hormone levels. Ninety subjects were randomly divided into two groups: a tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…HE has been demonstrated to decrease the total cholesterol and triglyceride levels, however to increase estradiol (13), and flavonoid components of HE have been reported to have antioxidant properties (14). HE flavonoids stimulate osteoblast formation and suppress the process of osteoclastogenesis in ovariectomized mice, and thus prevent bone loss in this model (15).…”
Section: Introductionmentioning
confidence: 99%
“…HE has been demonstrated to decrease the total cholesterol and triglyceride levels, however to increase estradiol (13), and flavonoid components of HE have been reported to have antioxidant properties (14). HE flavonoids stimulate osteoblast formation and suppress the process of osteoclastogenesis in ovariectomized mice, and thus prevent bone loss in this model (15).…”
Section: Introductionmentioning
confidence: 99%
“…However, no recurrence of menstruation was reported in any of the subjects. (32) Another clinical trial on 50 late postmenopausal women, who were randomised to take either herb-derived phyto-oestrogen flavonoids (60 mg icariin, 15 mg genistein and 3 mg daidzein) or a placebo daily for 24 months, reported no significant increase in the treatment group's serum oestradiol level. Interestingly, as with animal data, bone mineral density was maintained in the treatment group but was significantly reduced in the placebo group, without a concurrent hyperplasia effect on endometrium thickness.…”
Section: Herbs With Oestrogenic Activity Epimedium (Herba Epimedii Ymentioning
confidence: 99%
“…3 Phytoestrogens are assumed to produce minimal side effects and studies have shown that phytoestrogens are effective in the prevention and amelioration of the metabolism of sex hormones and blood lipids in women who are postmenopausal. 4 Asparagus racemosus (AR), also called shatavari, is a member of the familly Liliaceae, an Indian climbing plant. While in Thailand, AR is known as rak-sam-sib or sam-roi-rak.…”
Section: Introductionmentioning
confidence: 99%